Nocellara Del Belice (Olea europaea L. Cultivar): Leaf Extract Concentrated in Phenolic Compounds and Its Anti-Inflammatory and Radical Scavenging Activity - Vincenzo Musolino; Roberta Macrì; Antonio Cardamone; Maria Serra; Anna Rita Coppoletta; Luigi Tucci; Jessica Maiuolo; Carmine Lupia; Federica Scarano; Cristina Carresi; Saverio Nucera; Irene Bava; et al. (Plants, 2022)
Olea europaea L. is a plant belonging to the Oleaceae family, widely grown around the Mediterranean Basin and its leaves are a source of phenolic compounds with antioxidant and anti-inflammatory capacity. Among these, oleuropein and luteolin-7-O-glucoside represent two major polyphenolic compounds in olive-leaf extract. Herein, a polystyrene resin was used to recover the polyphenolic fraction from the acetone-water leaf extract from Nocellara del Belice cultivar, which showed the higher level of analysed bioactive compounds, compared to Carolea cultivar. The antioxidant activity of the extract concentrated in phenolic compounds (OLECp) was evaluated through a classical assay and electron paramagnetic resonance (EPR) for DPPH and hydroxyl radicals scavenging. Thus, the anti-inflammatory activity and the potential beneficial effects in reducing lipid accumulation in an in vitro model of NAFLD using McA-RH7777 cells exposed to oleic acid (OA) were evaluated. Nile Red and Oil Red O have been used to stain the lipid accumulation, while the inflammatory status was assessed by Cytokines Bioplex Assay. OLECp (TPC: 92.93 ± 9.35 mg GAE/g, TFC: 728.12 ± 16.04 mg RE/g; 1 g of extract contains 315.250 mg of oleuropein and 17.44 mg of luteolin-7-O-glucoside) exerted a good radical scavenging capability (IC50: 2.30 ± 0.18 mg/mL) with a neutralizing power against DPPH and hydroxyl radicals, as confirmed by the decreased signal area of the EPR spectra. Moreover, OLECp at concentration of 25, 50 and 100 μg/mL counteracted the intracellular inflammatory status, as result of decreased intracellular lipid content. Our results highlighted the multiple properties and applications of an O. europaea extract concentrated in polyphenols, and the possibility to formulate novel nutraceuticals with antioxidant properties, destined to ameliorate human health.